Anger Expression in Negotiation: The Effects of Communication Channels and Anger Intensity - Yun, Dongwon; Jung, Heajung (Frontiers in Psychology, 2022)
This research aimed to explore the effects of communication channels and anger intensity as factors determining how the expression of anger affects negotiation outcomes. Based on the ‘emotions as social information’ (EASI) model and media richness theory, we tried to examine how anger expression influences both economic and psychological negotiation outcomes as a function of communication channels and explore its underlying mechanism. In Study 1, 470 participants were randomly assigned to one of the five experimental conditionsneutral, anger expression via text/emoticon/ voice/videoand asked to participate in an online negotiation task. The results showed a significant main effect of communication channel; partner’s anger expression via communication channels richer in nonverbal cues (voice and video) led participants to make a higher concession and report lower satisfaction with negotiation and lower desire for future interaction with the same partner compared to anger expression via less rich channels (text and emoticon). The anger expression effects on psychological outcomes were partially explained by perceiver’s anger experience in response to anger display, which is consistent with the affective mechanism proposed by the EASI model. Study 2 examined whether the results of Study 1 could be attributable to the different levels of anger intensity perceived by the participants across different communication channels. Data analyses from 189 participants showed a significant main effect of anger intensity only with a desire for future interaction, but not with satisfaction and concession. The insignificant findings of the latter imply that the observed channel effect in Study 1 cannot be fully explained by the intensity effect.